ANALISIS YURIDIS PEMBATALAN PERJANJIAN SECARA SEPIHAK - Firman Rahmat Hidayat; R Risaldy Yanuar Risky (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Cancellation of agreement recognized by the Indonesian Civil Code and it has to qualify the terms of cancellations. Cancellation of the agreement, which results no agreement has ever been considered at all, brings new legal consequences for the parties in the agreement. The aims of this paper are to understand about the cancellation terms and legal consequences that caused by the cancellation of the agreement. This paper applied normative analysis method combined with statutory approach in its composition. Terms of cancellation of the agreement are non-fulfillment of agreement, the agreement must be a mutual agreement, and the cancellation is through the judge's decision. Agreement may be canceled if it not qualifies the terms of the agreement. Legal consequence towards the parties in the agreement is to recover just like the original state before the agreement happened.